Optoelectric‐Driven Wetting Transition on Artificially Micropatterned Surfaces With Long‐Range Virtual Electrodes - Riccardo Zamboni; Debdatta Ray; Cornelia Denz; Jörg Imbrock (Advanced Materials Interfaces)
Abstract The manipulation of droplets and wetting properties is crucial in many applications that involve surface‐liquid interactions, especially on artificial superhydrophobic substrates. This study presents an active optoelectronic method to achieve transport and transition between two wetting states on patterned surfaces, namely Cassie–Baxter (CB) and Wenzel (W). The approach employs a photovoltaic iron‐doped lithium niobate crystal placed on the bottom of a micropatterned substrate without any adhesive or sticky bonding. Taking advantage of the bulk photovoltaic effect, charge separation can be induced by light inside the crystal, thus leading to virtual electrodes. The long‐range interaction between these virtual electrodes and the droplets on the top of the substrate allows for transitions between wetting states and droplet transport. Superhydrophobic wetting transitions between Cassie–Baxter and Wenzel are observed on different substrates using this technique. The forces acting on the droplet that cause the transition are determined numerically. The evolution of droplet deformation and contact angle during the generation of the virtual electrode depends on the shape and intensity of the light beam used for photoinduction, as well as on the compositional properties of the crystal.